Minocycline-Induced Gum Pigmentation during Treatment for Acne Vulgaris - Jami Wang; Isabella Brown; Heidi Goodarzi (Case Reports in Pediatrics)
Minocycline, a type of tetracycline, is a broad-spectrum antibiotic that is commonly prescribed in dermatology for the treatment of acne vulgaris. Common side effects of minocycline include nausea, vertigo, and dizziness while less common side effects include hyperpigmentation. In this case study, we found an 18-year-old female who presented with dark blue pigmentation in her upper gum after using minocycline on and off for 4 years. After discontinuation of the minocycline for 2 years, the pigmentation decreased gradually.